A Transcriptomic Analysis Reveals Novel Patterns of Gene Expression During 3T3-L1 Adipocyte Differentiation - Sun, Wuping; Yu, Zhijian; Yang, Shaomin; Jiang, Changyu; Kou, Yanbo; Xiao, Lizu; Tang, Shuo; Zhu, Tao (Frontiers in Molecular Biosciences, 2020)
Background: Obesity is characterized by increased adipose tissue mass that results from increased fat cell size (hypertrophy) and number (hyperplasia). The molecular mechanisms that govern the regulation and differentiation of adipocytes play a critical role for better understanding of the pathological mechanism of obesity. However, the mechanism of adipocyte differentiation is still unclear. Objective: The present study aims to compare the gene expression changes during adipocyte differentiation in the transcriptomic level, which may help to better understand the mechanism of adipocyte differentiation. Methods: RNA sequencing technology, GO and KEGG analysis, quantitative RT-PCR and oil red O staining methods were used in this study. Results: A lot of genes were up- or down- regulated between each two differentiation stages of 3T3-L1 cells. GO and KEGG analysis revealed that lipid metabolism and oxidation-reduction reaction were mainly involved in the whole process of adipocyte differentiation. Decreased immune response and cell cycle, adhesion was occurred in the late phase of adipocyte differentiation, which was demonstrated by divergent expression pattern analysis. Moreover, quantitative RT-PCR results showed that the mRNA expression levels of Trpv4, Trpm4, Trpm5 and Trpm7 were significantly decreased in the differentiated adipocytes. On the other hand, the mRNA expression level of Trpv1, Trpv2, Trpv6 and Trpc1 were significantly increased in the differentiated adipocytes. Besides, the mRNA expression of TRPV2 and TRPM7 were also significantly increased in subcutaneous white adipose tissue from diet-induced mice. And the activation of TRPM7, TRPV1, and TRPV2 suppressed the differentiation of adipocyte. Conclusions: These data present the description of transcription profile changes during adipocyte differentiation and provides an in-depth analysis of the possible mechanisms of adipocyte differentiation. These data offer new insight into the understanding of the mechanisms of adipocyte differentiation.